Age-Associated Effects of a Concurrent Cognitive Task on Gait Speed and Stability During Narrow-Base Walking - Kelly, Valerie E. (2008)
BACKGROUND: In older adults, changes in speed and stability during walking are associated with impaired balance and increased fall risk. Narrow-base walking requires increased frontal plane stability and can be used to assess postural control while walking. Performance of a concurrent cognitive task (dual task) may further increase the complexity of walking, potentially allowing identification of individuals with instability that is not detected under single-task conditions. The purpose of this study was to examine age-associated effects of a cognitive task on speed and frontal plane stability during narrow-base walking. METHODS: Thirty-four healthy adults participated, categorized by age: <65, 65–74, and ≥75 years. Participants walked at a comfortable pace within a narrow path under both single- and dual-task conditions. We examined spatiotemporal variables and frontal plane center of mass (CoM) parameters using a 13-segment biomechanical model. RESULTS: Increasing age (p < .001) and the performance of a concurrent cognitive task (p < .001) were both associated with decreased speed, with no interaction between these factors. Frontal plane CoM displacement and velocity increased with increasing age (both p < .001), but dual-task performance had no effect on these variables (both p > .450). CONCLUSIONS: Age-associated changes in both speed and stability are observed during narrow-base walking. Among this sample of healthy older adults, the addition of a concurrent cognitive task resulted in reduced speed, with no effect on frontal plane stability. Further research is needed to determine if dual-task, narrow-base walking is a sensitive and specific approach to identifying older adults at risk for falls.